2001
DOI: 10.1046/j.1365-8711.2001.04491.x
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillations in a solar active region coronal loop

Abstract: The Solar Eclipse Corona Imaging System (SECIS) was used to record high‐cadence observations of the solar corona during the total solar eclipse of 1999 August 11. During the 2 min 23.5 s of totality, 6364 images were recorded simultaneously in each of the two channels: a white light channel, and the Fe xiv (5303 Å) ‘green line’ channel (T∼2 MK). Here we report initial results from the SECIS experiment, including the discovery of a 6‐s intensity oscillation in an active region coronal loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
105
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 17 publications
8
105
0
1
Order By: Relevance
“…For observational investigations on quasi-periodic fast-mode waves, Williams et al (2002) first reported a quasi-periodic fast wave that travels through the apex of an active-region coronal loop with a speed of 2100 km s −1 and a dominant period of six seconds. This event was observed during the total solar eclipse on 11 August 1999, with the Solar Eclipse Corona Imaging System (SECIS) instrument, which has a rapid cadence of 2.25 × 10 −2 seconds and a pixel size of 4.07 ′′ (Williams et al, 2001). This temporal resolution is sufficient to detect the short-period fast waves.…”
Section: Introductionmentioning
confidence: 99%
“…For observational investigations on quasi-periodic fast-mode waves, Williams et al (2002) first reported a quasi-periodic fast wave that travels through the apex of an active-region coronal loop with a speed of 2100 km s −1 and a dominant period of six seconds. This event was observed during the total solar eclipse on 11 August 1999, with the Solar Eclipse Corona Imaging System (SECIS) instrument, which has a rapid cadence of 2.25 × 10 −2 seconds and a pixel size of 4.07 ′′ (Williams et al, 2001). This temporal resolution is sufficient to detect the short-period fast waves.…”
Section: Introductionmentioning
confidence: 99%
“…However, application of rigorous statistical tests showed that none of these was significant. An earlier wavelet analysis (Williams et al, 2001) of the same data shows evidence of a travelling wave moving down the leg of a small loop, with periodicities of six seconds (0.16 Hz).…”
Section: Introductionmentioning
confidence: 84%
“…In the case of ground-based observations, when the loop is observed in the green line bandpass, the observability is limited by the spatial resolution of the telescope, which is usually over a few arcsec, as the time resolution of such observations is usually less then 1 s (e.g., the cadence time of SECIS is 2.25 × 10 −2 s and the pixel size is 4.07 arcsec, Williams et al 2001). In particular, this effect can be responsible for propagating 6 s disturbances of the Fe  green line, discovered by the stroboscopic method in a solar eclipse data and interpreted as fast magnetoacoustic waves (Williams et al 2002, see also Williams et al 2001.…”
Section: Discussionmentioning
confidence: 99%